Perlindungan Hukum Bagi Ahli Waris yang Tidak Tercantum sebagai Penerima Manfaat dalam Asuransi Jiwa - Sulistyorini, Hastuti; Hamidah, Siti; Sulistyarini, Rachmi (Universitas Negeri Malang, 2020)
The research objective was to find a form of legal protection that was given to heirs who were not listed as beneficiaries of insurance funds on a life insurance policy. The study used the normative juridical method by using the statute approach and the conceptual approach, the technique of gathering legal material through literature study, and the analysis technique was carried out prescriptive. The results of the study showed that heirs were the most interested parties as beneficiaries of life insurance funds. The heirs who were not listed as beneficiaries in the life insurance policy received legal protection in the form of external and internal legal protection. External legal protection was provided by legislation, while internal legal protection was provided by a life insurance policy that had been mutually agreed upon and under the principles of life insurance.